Polarization formula for (p,q)-polynomials on a complex normed space - Zagorodnyuk, A. V.; Vasylyshyn, T. V. (Methods of Functional Analysis and Topology, 2011)
The aim of this paper to give some analogues of polarization formulas and the polarization inequality for (p,q)-polynomials between complex normed spaces. Obtained results are useful for investigation of real-differentiable mappings on complex spaces.